Towards developing a web based online advisor system implemented for health care supplements / Mohamed Roshimi Md Shahor - Md Shahor, Mohamed Roshimi (2006)
Web based system moves forward to its advance development that provides information services through the internet around the world. Many researchers already knew the advantages and try to take out the system out of its box which is not only providing static information but also implements with other sort of system. One of implementation is web based system and expert system to develop a Web Based Online Advisor System that can communicate and interact with user. Currently Luxor Network Sdn. Bhd doesn't provide this service as an alternative of their strategy to establish good relationship with customers. The objectives of this research are to identify the user requirement for developing a Web Based Online Advisor System for Luxor Network Sdn Bhd., to design architecture of the Web Based Online Advisor System for Luxor Network Sdn Bhd based on the user requirement and to develop a Web Based Online Advisor System for Luxor Network Sdn Bhd based on the user requirement. The approach that I've been using is through interview and questionnaire analysis, and also using part of web based expert system methodology to develop this project. Through the methodology, I take out some steps such as knowledge acquisition and knowledge representation to come out with a Ust of useful rules for the project Through the approach and findings in this research, I manage to achieve the entire objective of my research mention above.